A method for synthesizing nanowires by step-by-step assembly of a silver-loaded zinc ion solution
The synthesis method of step-by-step assembly of grown nanowires by silver-loaded zinc-loaded ionic solution was solved, and nanosilver wires with high purity, low resistivity and good dispersion were achieved, reducing production costs and improving application performance.
Patent Information
- Application Number
- CN201910017432.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2019-01-08
- Publication Date
- 2025-05-09
- Estimated Expiration
- 2039-01-08
AI Technical Summary
The prior art has problems such as low particle purity, ink migration and flow, easy printing to short circuit and substrate pollution, poor particle dispersion, and high production costs when preparing nano silver wires, making it difficult to achieve large-scale production and high-quality preparation.
The synthesis method of step-by-step assembling the growth nanowires with silver-loaded zinc is adopted. Through multi-step solution treatment and assembly technology, including preparation of nanosilver and zinc oxygen seed solutions, preparation of precursor growth solutions, multiple growth and purification treatment, the nanowires are finally dispersed in organic solvents and resins to form coatable inks.
The high purity, good dispersion and low resistivity of nano silver wires are achieved, which solves the problems of low purity and poor dispersion of particles in traditional methods, reduces production costs, and improves the application performance of nano silver wires.
Smart Images

Figure CN111408730B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polycrystalline synthesis and assembly, in particular to a synthesis method for step-by-step assembly and growth of nanowires using a silver-loaded zinc ion solution, belonging to chemical polycrystalline nucleus cultivation technology. Summary of the invention
[0002] The application research of nanotechnology is developing rapidly in four major fields: AI semiconductor chips, cancer diagnosis, new optical materials, and biomolecule tracking. For example, nano-metal oxide semiconductor field effect transistors, luminescent nanoparticles and nanocomposites for flat panel displays, and nanophotonic crystals will emerge; single electron transistors for integrated circuits, memory and logic elements, and molecular chemical assembly computers will be put into use; the control and self-assembly of molecules and atomic clusters, quantum logic devices, molecular electronic devices, medical intelligent nanorobots, integrated biochemical sensors, etc. will be studied and manufactured.
[0003] From the perspective of technological development trends, organic polymer nanosilver conductive ink that can be cured at room temperature, has good mechanical properties and carrier capacity, environmentally friendly water-soluble, wettable conductivity, and nano-surface interface small-size tunnel quantum effect will be the direction of future development.
[0004] Using PVP and CTAB rod-shaped micelles as templates, using pure chemical reduction methods, and seed-induced growth, rod-shaped nanoparticles can be prepared. The key to this method is to use seeds to induce the growth of nanoparticles and rod-shaped micelle agents that provide a suitable environment for the growth of nanorods. There are many silver ions around the seeds, which can be reduced to silver atoms after adding a reducing agent and deposited around the seeds, causing the nanoparticles to continue to grow. Since the seeds are in rod-shaped micelle agents, their lateral growth is restricted, forcing them to grow only in the longitudinal direction. The first induced growth can obtain a wire with a diameter of about 1nm, and 2-3 induced growths can reach 20nm, 50-500nm in length, and the average aspect ratio (the ratio of the longest diameter inside the particle to the longest diameter perpendicular to it) is about 5000um silver wire. If the growth is continued with modification and cultivation, longer wire rods can be obtained.
[0005] This method is through the use of cationic surfactants (hexadecyltrimethylammonium bromide). When the concentration of the surfactant exceeds a certain pH value, it will associate from single ions or molecules to form colloidal aggregates, ordered combinations of molecules, various array micelles, without any toxic emissions. The production process is simple, the cost is low, the particle size is small, and the curing temperature is low. The curing temperature of 70-150°C can smoothly generate substrate-free nanofilms, and further optimize the substrate function to improve the quality. Different surfactants have different structures and charge properties, different concentrations, and different forms of existence in aqueous solutions. They can form self-assemblies such as micelles, liquid crystals and vesicles in the solution. Therefore, they can be used as ideal templates for the synthesis of nanomaterials, and even these clusters themselves are the prototypes of nanoparticles. Summary of the invention
[0007] In view of this, the present invention provides a method for synthesizing nanowires by step-by-step assembly of a silver-loaded zinc ion solution. To achieve the above-mentioned purpose, the method comprises the following steps:
[0008] S1. Nanosilver Ag seed solution: Dissolve AgN03 in deionized water until the AgN03 is completely dissolved, add the protective agent, stir vigorously, and then dissolve the protective agent and reducing agent in ice-cold deionized water. Continue stirring for 10 min and then stop. Place at room temperature for 2 days for use. The solution turns orange;
[0009] S2, nano ZnO seed solution: dissolve zinc nitrate hexahydrate in anhydrous ethanol, add sodium hydroxide to reduce it into hexagonal crystal zinc powder, wash it several times, filter it, dissolve it again and disperse it into seed solution;
[0010] S3, Precursor growth solution: Adjust AgN03 and hexadecyltrimethylammonium bromide (CTAB) to a certain concentration, add them to ultrapure water, heat and stir at about 40°C until the solute is completely dissolved and the solution is completely clear and transparent. This solution is the growth solution, which is left to cool to room temperature for use;
[0011] S4, synthesizing the first growth solution of the assembly: the solution of step S3 is transferred into a reaction vessel, 1-10% ascorbic acid C6H806 is added and stirred evenly, then different amounts of S1 solution and S2 are mixed and stirred evenly, and then an appropriate amount of mL sodium hydroxide (NaOH, 1 mol / L) is added to initiate growth, hexadecyltrimethylammonium bromide is used to adjust the pH value, and a PVP wrapping agent (soft film board) is added. By changing the time, temperature, and vapor pressure parameters for 2-3 hours, it is grown in the micelle into nanometer 0.1-10 nanometer particles, and the first grown Ag+ZnO assembly powder is obtained, which is marked as Agl solution;
[0012] S5, cultivating the second growth of Agl solution: Measure 20 mL of the growth solution in step S3, add 0.2 mL of ascorbic acid and (0.1 mol / L) of polyol respectively, mix and stir again, add different amounts of Agl solution in step S4 to this solution and mix evenly, then add 0.1 mL of NaOH (1 mol / L) to induce growth again, add PVP encapsulating agent (soft film board) to obtain the second grown particles with a diameter of 1-25 nm, marked as Ag2;
[0013] S6, Ag2 solution purification: impurity removal, active agent surface attachment cleaning;
[0014] S7, dispersion process formula: dispersing ZnOAg powder in organic solvent and resin;
[0015] S8. Characterization test: Functional test after film formation. The coatable ink is formed and coated on the substrate using a slot-type coating and printing process. After coating, the surface is dried at room temperature and then placed in a constant temperature drying oven and cured at 80°C for 2 hours for performance testing.
[0016] As a further improvement of the present invention, the mixed liquid configuration ratio is: the protective agent and the reducing agent are dissolved in the organic solvent and stirred evenly, the mass ratio of the reducing agent to the organic solvent is {1:0.015~2.5:2.0~7.5} in the dispersed solution, the protective agent can be PVP and ascorbic acid, the reducing agent can be sodium borohydride (NaBH4) and polyol, 8mL of PVP is added to a certain amount of deionized water, and then added to 0.375ml / L of polyol solution and stirred evenly, 6ml of 0.1moI / L AgNo3 ethylene glycol solution is added at one time within 20 seconds, the temperature is controlled at 100-180℃, and the heating is stopped after 1 hour.
[0017] As a further improvement of the present invention, during the reaction process, the rotor speed is 600-1200r / min, the reaction color changes from yellow to orange, and finally to grayish white, and then 3-5 times the amount of acetone in the reaction solution is added to the reaction solution, ultrasonic cleaning is performed, and the product can be placed in a centrifuge with a speed of 5000-10000r / for separation for 45min as needed to remove the organic solvent attachment, and the precipitate is dispersed in anhydrous ethanol to obtain the material in the desired step.
[0018] As a further improvement of the present invention, a polyglycol solution with a mass fraction of 150 ML, 22.3% zinc nitrate and 0, 1%, 5%, and 7% silver nitrate in atomic percentages are added to prepare a zinc-silver mixed solution.
[0019] As a further improvement of the present invention, 150°C is the critical temperature for the growth of nano silver wires, and the optimal welding process parameters for thermal welding under a protective atmosphere are 0.9×104Pa, 150°C, 1h. After welding, the resistivity drops to only 60% of the original value.
[0020] As a further improvement of the present invention, the size of the wire rods can be changed by changing the concentration of the aqueous solution. After one hour of reaction, the diameter of the nanowire rods is 10-20nm, the length is 100um, the C axis is perpendicular to the substrate, and it has a tendency to preferentially grow along the crystal direction. The pH value is around 10, and the direction is best, forming a nanorod array.
[0021] As a further improvement of the present invention:
[0022] The first step is to soak the Ag2 solution in a manganese sulfate solution and heat it to 10-70°C for 10-30 minutes, take out the precipitate and filter it, add 3-4 times of deionized water and stir to dilute it evenly;
[0023] The second step is to filter the diluted solution through a membrane to obtain a filtrate. The membrane filtration is selected from reverse osmosis membrane filtration or ceramic membrane filtration, wherein the pore size of the reverse osmosis membrane or ceramic membrane is selected to be 25 nm, and the pressure of the membrane filtration is 0.2 atmosphere to 50 atmospheres;
[0024] Step 3: Centrifuge and wash (10000 r / min, 10 rain) 3 times, ultrasonic wash 2 times, concentrate to 10 mL for use. After purification again, dry to form linear composite ZnOAg crystal composition powder.
[0025] As a further improvement of the present invention, the ink formula is: 0.1-5% of nano silver wire; 1-12% of water-based resin; organic solvent: 10-45% of isopropyl alcohol; 0.1-5% of conductive high molecular polymer, and 30-90% of deionized water.
[0026] As a further improvement of the present invention, 1.5 g of synthesized ZnOAg (3% by atom) nanopowder was dispersed in 10 mL of butanone, ultrasonicated for 10 min, and the obtained solution was added to 15 g of polyacrylic acid resin, and a defoamer with a mass fraction of 0.8% was added, stirred vigorously to form a uniform and stable solution, and allowed to stand for 10 min. The coating prepared above was coated on a 26.5 cm × 26.5 cm flat glass using a 50 μm wire rod coater (the glass surface was pretreated with sodium hydroxide solution, distilled water and anhydrous ethanol before coating to make the glass surface clean and free of impurities). After coating, the surface was dried at room temperature, and then placed in a constant temperature drying oven and cured at 80 ° C for 2 h to form a film for thermal insulation performance testing.
[0027] Compared with the prior art, the beneficial effects of the present invention are: the material has excellent superconducting flux creep activation energy, anti-electromigration, superplastic ductility, dispersibility, high purity, narrow particle size distribution, high conductivity and the function of increasing contact points and reducing the spacing between particles in the dispersion; it can play a key role in large integration, high-density storage and ultra-fast transmission, thin wires, multi-layer intelligent digital printing and polymer carbonization, improving the catalytic performance of oxidases, enhancing Raman spectroscopy SERS matrix, and electromagnetic wave shielding materials.
[0028] This production method is simple and easy, and there is no emission of toxic substances. It has unique antibacterial properties and optical conductivity, and has multifunctional uses. It is widely used in chemical reactions, optical fields, biomaterials, medical fields, environmental protection, military fields, etc., and can play the functions of conduction, heating, electrode, field emission, electromagnetic shielding and wave absorption in these fields.
[0029] This method is aimed at enterprises in the current industry. The preparation process has low particle purity, ink migration and flow, printing is prone to wire short circuit and substrate pollution, particle dispersion is poor, only low concentration system is practical, and only tens of milligrams of nano silver wires are obtained each time, which is not conducive to mass production of silver wires. It is difficult to control the morphology, the production cost is high, the investment is large, the high curing temperature is easy to damage the substrate, and the transmittance is <90. These problems are completely solved and improved.
[0030] This method has been repeatedly tested for multiple parameter data, successfully achieving the best formula for tension matching between the base film and the nano silver wire ink, and improving its coating performance. It realizes the selection of auxiliary solvents in the silver wire ink, solves the pain point of mutual agglomeration of nano silver wires, solves the uniformity of the resistance of the silver wire transparent conductive film, and finds the coating thickness suitable for the mass fraction of each ink, and strictly controls the thickness change. Its convenient temperature control technology and reasonable process formula are a major feature of this technology. It forms a situation where the actual nano metal particle size is small and the resistance is low. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0032] Figure 1 The present invention is a method for synthesizing a silver-loaded zinc ion solution to assemble and grow heterojunction nanowires in steps, and a schematic diagram of a method flow chart of a specific implementation method. DETAILED DESCRIPTION
[0033] The present invention discloses a method for synthesizing nanowires by step-by-step assembly of a silver-loaded zinc ion solution, which comprises the following steps:
[0034] S1. Nanosilver Ag seed solution: Dissolve AgN03 in deionized water until the AgN03 is completely dissolved, add the protective agent, stir vigorously, and then dissolve the protective agent and reducing agent in ice-cold deionized water. Continue stirring for 10 min and then stop. Place at room temperature for 2 days for use. The solution turns orange;
[0035] S2, nano ZnO seed solution: dissolve zinc nitrate hexahydrate in anhydrous ethanol, add sodium hydroxide to reduce it into hexagonal crystal zinc powder, wash it several times, filter it, dissolve it again and disperse it into seed solution;
[0036] S3, Precursor growth solution: Adjust AgN03 and hexadecyltrimethylammonium bromide (CTAB) to a certain concentration, add them to ultrapure water, heat and stir at about 40°C until the solute is completely dissolved and the solution is completely clear and transparent. This solution is the growth solution, which is left to cool to room temperature for use;
[0037] S4, synthesizing the first growth solution of the assembly: the solution of step S3 is transferred into a reaction vessel, 1-10% ascorbic acid C6H806 is added and stirred evenly, then different amounts of S1 solution and S2 are mixed and stirred evenly, and then an appropriate amount of mL sodium hydroxide (NaOH, 1 mol / L) is added to initiate growth, hexadecyltrimethylammonium bromide is used to adjust the pH value, and a PVP wrapping agent (soft film board) is added. By changing the time, temperature, and vapor pressure parameters for 2-3 hours, it is grown in the micelle into nanometer 0.1-10 nanometer particles, and the first grown Ag+ZnO assembly powder is obtained, which is marked as Agl solution;
[0038] S5, cultivating the second growth of Agl solution: Measure 20 mL of the growth solution in step S3, add 0.2 mL of ascorbic acid and (0.1 mol / L) of polyol respectively, mix and stir again, add different amounts of Agl solution in step S4 to this solution and mix evenly, then add 0.1 mL of NaOH (1 mol / L) to induce growth again, add PVP encapsulating agent (soft film board) to obtain the second grown particles with a diameter of 1-25 nm, marked as Ag2;
[0039] S6, Ag2 solution purification: impurity removal, active agent surface attachment cleaning;
[0040] S7, dispersion process formula: dispersing ZnOAg powder in organic solvent and resin;
[0041] S8. Characterization test: Functional test after film formation. The coatable ink is formed and coated on the substrate using a slot-type coating and printing process. After coating, the surface is dried at room temperature and then placed in a constant temperature drying oven and cured at 80°C for 2 hours for performance testing.
[0042] The performance of the nanofilm prepared by the synthesis method of the present invention of step-by-step assembly and growth of nanowires using a silver-loaded zinc ion solution is tested by a test experiment:
[0043] (1) Adhesion: Stick 3M600# adhesive tape on the cured printed sample line. The conductive line is 10 cm long, 0.9 mm wide and 3 μm thick. Make sure the long side of the adhesive tape is parallel to the conductive line. Use a high-grade drawing eraser to smooth it. After leaving it for 1 minute, pull off the tape vertically and quickly. Observe whether the film layer of the tape and the sample line is pulled off. Measure the change in line resistance before and after adhesion. Measure 5 parallel values for each conductive line and take the average value.
[0044] (2) Coating wear resistance and pencil hardness test: using a vibration wear tester, the product is placed in a special liquid mixed with colored stones and potion, and subjected to vibration friction to test the product's wear resistance. The test results are as follows: the metal nanofilm of the present invention meets the ASTM D 3363-74 standard and the ASTM D 3363-00 coating pencil hardness standard, reaching 5H;
[0045] (3) Transmission electron microscopy (TEM) (JEOL 200CX, working voltage 200 kV) was used to analyze the morphology, dispersion and other characteristics of silver nanowires. See the performance parameter table below:
[0046]
[0047] (4) Curing behavior: Differential scanning thermal analysis (DSC) was performed using a PerkinElmer DSC-7 thermal analyzer in a static air atmosphere. The temperature was increased for curing. The DSC heating rate was 10°C / min and the temperature range was 35-180°C.
[0048] (5). The bending resistance of the flexible circuit board was tested using the Tosda TOS-817 swing tester. The conductive line was 2.4 cm long, 0.9 mm wide, and 3 μm thick. Five parallel values were measured and the average value was taken. The experimental parameters are as follows: swing angle: 180°; swing speed: 60 times / min-1; swing number: 10,000 times; temperature: 28°C, relative humidity: 80%.
[0049] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered exemplary and non-limiting in all respects, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations falling within the meaning and scope of the equivalent elements of the claims be included in the invention. Any reference numeral in a claim should not be considered as limiting the claim to which it relates.
[0050] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This narrative method of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.
Claims
1. A method for synthesizing nanowires by step-by-step assembly of a silver-loaded zinc ion solution, characterized in that: The synthesis method comprises the following steps: S1. Nanosilver Ag seed solution: Dissolve AgN03 in deionized water until the AgN03 is completely dissolved, add the protective agent, stir vigorously, and then dissolve the protective agent and reducing agent in ice-cold deionized water. Continue stirring for 10 minutes and then stop. Place at room temperature for 2 days for use. The solution turns orange; S2, nano ZnO seed solution: dissolve zinc nitrate hexahydrate in anhydrous ethanol, add sodium hydroxide to reduce it into hexagonal crystal zinc powder, wash it several times, filter it, dissolve it again and disperse it into seed solution; S3, precursor growth solution: adjust AgN03 and hexadecyltrimethylammonium bromide to a certain concentration, add them into ultrapure water, heat and stir at about 40°C until the solute is completely dissolved and the solution is completely clear and transparent. This solution is the growth solution, which is left to cool to room temperature for use; S4, synthesizing the first growth solution of the assembly: the solution of step S3 is transferred into a reaction vessel, 1-10% ascorbic acid C6H806 is added and stirred evenly, then different amounts of S1 solution and S2 are mixed and stirred evenly, and then an appropriate amount of NaOH in mL of 1 mol / L is added to initiate growth, and hexadecyltrimethylammonium bromide is used to adjust the pH value and add the PVP wrapping agent soft film plate, and by changing the time, temperature and vapor pressure parameters for 2-3 hours, it is grown into nanometer 0.1-10 nanometer particles in the micelle to obtain the first grown Ag+ZnO assembly powder, which is marked as Agl solution; S5, cultivating the second growth of Agl solution: 20 mL of the growth solution in step S3 was measured, and 0.2 mL of ascorbic acid and 0.1 mol / L of polyol were added respectively, and the mixture was stirred evenly again, and then different amounts of the Agl solution in step S4 were added to the solution and mixed evenly, and then 0.1 mL of 1 mol / L NaOH was added to induce growth again, and a PVP wrapping agent soft film plate was added to obtain the second grown particles with a diameter of 1-25 nm, which were marked as Ag2; S6, Ag2 solution purification: impurity removal, active agent surface attachment cleaning; S7, dispersion process formula: dispersing ZnOAg powder in organic solvent and resin; S8. Characterization test: Functional test after film formation. The coatable ink is formed and coated on the substrate using a slit coating and printing process. After coating, the surface is dried at room temperature and then placed in a constant temperature drying oven and cured at 80°C for 2 hours for performance testing.
2. The method for synthesizing nanowires by step-by-step assembly of a silver-loaded zinc ion solution according to claim 1, characterized in that: The preparation method comprises the following steps, characterized in that the protective agent and the reducing agent in step S1, step S2, step S3, step S4 and step S5 are dissolved in an organic solvent and stirred evenly, the mass ratio of the reducing agent to the organic solvent is {1:0.015-2.5:2.0-7.5} in the dispersed solution, the protective agent can be PVP and ascorbic acid, the reducing agent can be sodium borohydride and polyol, 8 mL of PVP is added to a certain amount of deionized water, and then added to 0.375 ml / L of polyol solution and stirred evenly, 6 ml of 0.1 mol / L AgNo3 ethylene glycol solution is added at one time within 20 seconds, the temperature is controlled at 100-180°C, and the heating is stopped after 1 hour.
3. The method for synthesizing nanowires by step-by-step assembly of a silver-loaded zinc ion solution according to claim 1, characterized in that: Features: In step S1, step S2, step S3, step S4 and step S5, the rotor speed during the reaction is 600-1200 r / min, the reaction color changes from yellow to orange, and finally to grayish white, and then 3-5 times the amount of acetone in the reaction solution is added to the reaction solution, and ultrasonic cleaning is performed. If necessary, the product can be placed in a centrifuge with a speed of 5000-10000 r / min for separation for 45 minutes to remove the organic solvent attachment, and the precipitate is dispersed in anhydrous ethanol to obtain the material in the required step.
4. The method for synthesizing nanowires by step-by-step assembly of a silver-loaded zinc ion solution according to claim 1, characterized in that: In the step S2, 150 ml of polyglycol solution, 22.3% zinc nitrate and 0, 1, 5 and 7 atomic percent silver nitrate are added to prepare a zinc-silver mixed solution.
5. The method for synthesizing nanowires by step-by-step assembly of a silver-loaded zinc ion solution according to claim 1, characterized in that In step S4 and step S5: 150°C is the critical temperature for the start of growth of nano silver wires. The optimal welding process parameters for thermal welding under a protective atmosphere are 0.9×104Pa, 150°C, 1h. After welding, the resistivity drops to only 60% of the original value.
6. The method for synthesizing nanowires by step-by-step assembly of a silver-loaded zinc ion solution according to claim 1, characterized in that: As described in step S5: the size of the wire rods can be changed by changing the concentration of the aqueous solution. After reacting for 1 hour, the diameter of the nanowire rods is 10-20nm, the length is 100um, the C axis is perpendicular to the substrate, and there is a tendency to preferentially grow along the crystal direction. The pH value is about 10, and the direction is best, forming a nanorod array.
7. The method for synthesizing nanowires by step-by-step assembly of a silver-loaded zinc ion solution according to claim 1, characterized in that: In step S6: The first step is to soak the Ag2 solution in a manganese sulfate solution and heat it to 10-70°C for 10-30 minutes, take out the precipitate and filter it, add 3-4 times of deionized water and stir to dilute it evenly; The second step is to filter the diluted solution through a membrane to obtain a filtrate, wherein the membrane filtration is selected from reverse osmosis membrane filtration or ceramic membrane filtration, wherein the pore size of the reverse osmosis membrane or the ceramic membrane is selected to be 25 nm, and the pressure of the membrane filtration is 0.2 atmosphere to 50 atmospheres; Step 3: centrifuge and wash for 3 times at 10000 r / min, 10 rain, ultrasonic wash for 2 times, concentrate to 10 mL for standby use; purify again and dry to form linear composite ZnOAg crystal composition powder.
8. The method for synthesizing nanowires by step-by-step assembly of a silver-loaded zinc ion solution according to claim 1, characterized in that: In step S7, the ink formula is: 0.1-5% of nano silver wire; 1-12% of water-based resin; organic solvent: 10-45% of isopropyl alcohol; 0.1-5% of conductive polymer; and 30-90% of deionized water.
9. The method for synthesizing nanowires by step-by-step assembly of a silver-loaded zinc ion solution according to claim 1, characterized in that: In step S8: 1.5g of synthesized ZnOAg nanopowder with an atomic percentage of 3% was dispersed in 10mL of butanone, and ultrasonicated for 10min. The obtained solution was added to 15g of polyacrylic acid resin, and a defoamer with a mass fraction of 0.8% was added. The solution was stirred vigorously to form a uniform and stable solution, and then allowed to stand for 10min. The above-prepared coating was applied to a 26.5cm×26.5cm flat glass using a 50μm wire rod coater. Before coating, the glass surface was pretreated with sodium hydroxide solution, distilled water and anhydrous ethanol to make the glass surface clean and free of impurities. After coating, the surface was dried at room temperature, and then placed in a constant temperature drying oven and cured at 80℃ for 2h to form a film for thermal insulation performance test.
Citation Information
Patent Citations
Process for producing silver doped zinc oxide nano-stick
CN101508459A
Method for microwave synthesis of nano-ZnO assembled cotton fibers
CN103194885A